CONTEMPORARY TOOLS OF STRATEGIC CONTROLLING IN THE MANAGEMENT OF INDUSTRIAL ENTERPRISES - Yu.E. Dudnieva; O.I. Кirian (Економіка та право)
The article is devoted to the study of the essence, functions, tasks and tools of strategic controlling in the management of industrial enterprises. Strategic control is considered by the authors as a management methodology. The main content of controlling is the rationale for the interaction of the enterprise with the external environment, the identification of cause and effect relations of strategic problems, the identification of possible priority ways for the development of an industrial enterprise. It is emphasized that strategic controlling allows to adapt the parameters of the industrial enterprise to the parameters and risks of the external environment, to identify the discrepancy of the development strategy with the existing market requirements and their predicted trends. It is proved that strategic controlling can be applied in various modifications in any large enough enterprises, it must correspond to the strategic plans of the enterprise, not to substitute for strategic management, but to help the successful implementation of the strategy. The tools of strategic controlling are considered as a set of actions aimed at performing controlling functions. The system of strategic controlling tools is investigated, the application of which makes it possible to solve its tasks. Summarized information on the features and prospects for implementing specific tools of strategic controlling in practical managerial activities. The tools of strategic controlling are considered as a set of actions aimed at performing controlling functions. The system of strategic controlling tools is investigated, the application of which makes it possible to solve its tasks. Generalized information about the peculiarities and prospects for the implementation of certain specific instruments of strategic controlling in practical managerial activities. It is determined that the instruments of strategic controlling in case of their successful integrated use can actually influence the efficiency and adequacy of managerial decisions, increasing the overall level of management of the enterprise. Prospects for further research on a specific issue are the implementation of strategic controlling tools on a system-by-package basis, which will allow industrial enterprises, in conditions of uncertainty in the external environment, to maintain and strengthen their own competitiveness and develop their strategic potential.